Penerapan Sistem Informasi Untuk Identifikasi Literasi Pada Siswa Disabilitas Taman Kanak-Kanak Dan Siswa Sekolah Dasar - Harianto, Harianto; Aziz, Abdul; Hamdi, Muhammad (Fakultas Teknik Universitas Hamzanwadi, 2024)
Students with disabilities are students who experience physical, intellectual, mental and/or sensory limitations for a long period of time, who in interacting with the environment can experience obstacles and difficulties in participating fully and effectively with the people around them. Students with disabilities need special ways and methods to determine children's development, especially in their reading literacy. Children's reading comprehension levels need to be measured and tested to make it easier to group study groups. The grouping of children's reading comprehension is grouped based on the child's level of understanding, namely basic level, letter level, word level, sentence level, paragraph level and description level. Grouping can be done by testing and measuring children's level of understanding based on these levels. This can be done quickly and accurately if supported by an information system that answers these needs. The aim of this research is to create an information system for mapping the reading literacy of students with disabilities against student difficulties. The system also makes it easier for teachers or agencies to identify children's reading abilities so that they can be grouped based on level and difficulty